Universal Synthesized Strategy for Amorphous Pd‐Based Nanosheets Boosting Ambient Ammonia Electrosynthesis. Issue 1 (22nd December 2022) - Dong, Zemeng; Sun, Qiyan; Xu, Guang‐Rui; Wu, Zexing; Li, Yanyan; Lai, Jianping; Li, Guangjiu; Wang, Lei
Abstract: The electrocatalytic nitrogen reduction reaction (NRR) is emerging as a great promise for ambient and sustainable NH3 production while it still suffers from the high adsorption energy of N2, the difficulty of *NN protonation, and inevitable hydrogen evolution, leading to a great challenge for efficient NRR. Herein, we synthesized a series of amorphous trimetal Pd‐based (PdCoM (M = Cu, Ag, Fe, Mo)) nanosheets (NSs) with an ultrathin 2D structure, which shows high efficiency and robust electrocatalytic nitrogen fixation. Among them, amorphous PdCoCu NSs exhibit excellent NRR activity at low overpotentials with an NH3 yield of 60.68 µg h −1 mgcat −1 and a corresponding Faraday efficiency of 42.93% at −0.05 V versus reversible hydrogen electrode as well as outstanding stability with only 5% decrease after a long test period of 40 h at room temperature. The superior NRR activity and robust stability should be attributed to the large specific surface area, abundant active sites as well as structural engineering and electronic effect that boosts up the Pd 4d band center, which further efficiently restrains the hydrogen evolution. This work offers an opportunity for more energy conversion devices through the novel strategy for designing active and stable catalysts. Abstract : A series of amorphous trimetal Pd‐based (PdCoM (M = Cu, Ag, Fe, Mo)) nanosheets (NSs) is synthesized by a universal one‐pot solvothermal method, in which the amorphous PdCoCu NSs exhibit excellent nitrogen reduction reaction activity and stability at low overpotentials due to the structural engineering of the porous ultrathin architecture and electronic effect boosting up the Pd 4d band center.